Application of Langmuir Isotherms to Describe Zinc and Copper Adsorption in Some Gypsiferous Soils - Mahmood Ahmed L. Al-Bayati; Yasir Hmood Ijresh AL-janabi; Basim Shakir Obaid AL-Obaidi (مجلة ديالى للعلوم الزراعية)
This study aims to evaluate and compare the adsorption behavior of copper and zinc in some gypsiferous soils using the linearization methods of the Langmuir equation. Six surface soil samples were taken from three different sites in Salah al-Din and Najaf governorates. Coefficient of determination (R²) was high for both ions, except for zinc in Salah al-Din site T3. Langmuir equation constants showed maximum adsorption values (b) higher for copper than zinc, reaching 476.19 mg kg-1 in Salah al-Din site T3 and 1666.66 mg kg-1 in Najaf site N3. Zinc's highest values were 181.81 mg kg-1 in Salah al-Din site T2 and 666.66 mg kg-1 in Najaf N3. The results indicated that the high maximum adsorption values (b) for both ions are associated with a relatively low binding energy (k). The results also confirmed that copper ions had much lower binding energy values than zinc ions, with copper at 15 L mg-1 in Salah al-Din site T1 soil and 4 L mg-1 in Najaf site N2 soil. In contrast, zinc showed higher binding energy, with 122.54 L mg-1 in Salah al-Din T3 and 143.33 L mg-1 in Najaf N1. Copper’s distribution coefficient values are generally higher than zinc’s, except in Salah al-Din T3 and Najaf N1 soils. The results regarding the constants of the Langmuir equation for both ions indicated that the maximum adsorption value (b) indicates the soil's capacity to adsorb metals. Thus, the soil has a higher affinity for copper than for zinc.